Non-parametric analysis of the spatio-temporal variability in the fatty-acid profiles among Greenland sharks. (28th October 2016) - Steeves, Holly N.; Mcmeans, Bailey; Field, Chris; Stewart, Connie; Arts, Michael T.; Fisk, Aaron T.; Lydersen, Christian; Kovacs, Kit M.; Macneil, M. Aaron
Abstract : Shifting prey distributions due to global warming are expected to generate dramatic ecosystem-wide changes in trophic structure within Arctic marine ecosystems. Yet a relatively poor understanding of contemporary Arctic food webs makes it difficult to predict the consequences of such changes for Arctic predators. Doing so requires quantitative approaches that can track contemporary changes in predator diets through time, using accurate, well-defined methods. Here we use fatty acids (FA) to quantify differences in consumer diet using permutational multivariate analysis of variance tests that characterize spatial and temporal changes in consumer FA signatures. Specifically we explore differences in Greenland shark ( Somniosus microcephalus ) FA to differentiate their potential trophic role between Svalbard, Norway and Cumberland Sound, Canada. Greenland shark FA signatures revealed significant inter-annual differences, probably driven by varying seal and Greenland halibut responses to environmental conditions such as the NAO, bottom temperature, and annual sea-ice extent. Uncommon FA were also found to play an important role in driving spatial and temporal differences in Greenland shark FA profiles. Our statistical approach should facilitate quantification of changing consumer diets across a range of marine ecosystems.